Biochemical and physical characterisation of urinary nanovesicles following CHAPS treatment. - Luca Musante (Public Library of Science (PLoS), 2012)
Urinary exosomes represent a precious source of potential biomarkers for disease biology. Currently, the methods for vesicle isolation are severely restricted by the tendency of vesicle entrapment, e.g. by the abundant Tamm-Horsfall protein (THP) polymers. Treatment by reducing agents such as dithiothreitol (DTT) releases entrapped vesicles, thus increasing the final yield. However, this harsh treatment can cause remodelling of all those proteins which feature extra-vesicular domains stabilized by internal disulfide bridges and have detrimental effects on their biological activity. In order to optimize exosomal yield, we explore two vesicle treatment protocols - dithiothreitol (DTT) and 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic (CHAPS) - applied to the differential centrifugation protocol for exosomal vesicle isolation. The results show that CHAPS treatment does not affect vesicle morphology or exosomal marker distribution, thus eliminating most of THP interference. Moreover, the recovery and preservation of catalytic activity of two trans-membrane proteases, dipeptidyl peptidase IV and nephrilysin, was examined and found to be clearly superior after CHAPS treatment compared to DTT. Finally, proteomic profiling by mass spectrometry (MS) revealed that 76.2% of proteins recovered by CHAPS are common to those seen for DTT treatment, which illustrates underlining similarities between the two approaches. In conclusion, we provide a major improvement to currently-utilized urinary vesicle isolation strategies to allow recovery of urinary vesicles without the deleterious interference of abundant urinary proteins, while preserving typical protein folding and, consequently, the precious biological activity of urinary proteins which serve as valuable biomarkers.